The Social Tax: Redistributive Pressure and Labor Supply - Eliana Carranza; Aletheia Donald; Florian Grosset; Supreet Kaur (Institute of Labor Economics (IZA), 2022)
In low-income communities in both rich and poor countries, redistributive transfers within kin and social networks are frequent. Such arrangements may distort labor supply—acting as a "social tax" that dampens the incentive to work. We document that across countries, from Cote d'Ivoire to the United States, social groups that undertake more interpersonal transfers work fewer hours. Using a field experiment, we enable piece-rate factory workers in Côte d'Ivoire to shield income using blocked savings accounts over 3-9 months. Workers may only deposit earnings increases, relative to baseline, mitigating income effects on labor supply. We vary whether the offered account is private or known to the worker's network, altering the likelihood of transfer requests against saved income. When accounts are private, take-up is substantively higher (60% vs. 14%). Offering private accounts sharply increases labor supply— raising work attendance by 10% and earnings by 11%. Outgoing transfers do not decline, indicating no loss in redistribution. Our estimates imply a 9-14% social tax rate. The welfare benefits of informal redistribution may come at a cost, depressing labor supply and productivity.
Keywords: J22; J24; H24; D61; O12; 330; kin tax; informal insurance; illiquid savings; transfers; labor supply